2000
DOI: 10.1080/095008300176443
|View full text |Cite
|
Sign up to set email alerts
|

Bubble sorting in a foam under forced drainage

Abstract: A highly polydisperse foam is subjected to a constant liquid¯ow from above. For su ciently high¯ow rates, large-scale bubble motion is observed, in the course of which large bubbles rise to the top of the foam until a steady state is reached at which the average bubble size increases smoothly with height.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…4 remains elusive at this stage. There have been experiments with 3D foams [33] for which avalanches of rearrangements following an increase in liquid fraction have been observed, but there is no statistical data available.…”
Section: P(n) = λ Exp(−λn) (4)mentioning
confidence: 99%
“…4 remains elusive at this stage. There have been experiments with 3D foams [33] for which avalanches of rearrangements following an increase in liquid fraction have been observed, but there is no statistical data available.…”
Section: P(n) = λ Exp(−λn) (4)mentioning
confidence: 99%
“…Previous work, including experiments and simulations [7,8,9,10], show that vertical arrangements of foams have bigger and drier bubbles at the top and, smaller and wetter bubbles at the bottom. These experiments were performed for twodimensional foams of various levels of polydispersity; despite this, the results are loosely comparable to our case of a thin foam front in porous media.…”
Section: Slumpingmentioning
confidence: 99%
“…Those few studies that do report a bubble size distribution generally do so by photographing bubbles through the wall of the column and then sizing. For instance, Hutzler et al [5] investigated bubble sorting under forced drainage and reported bubble size distributions that were, on normalising [6], found to exhibit an approximately lognormal distribution. The foam in a beer head was found to be approximately log-normally distributed too [7].…”
Section: Introductionmentioning
confidence: 99%